Suitable gibberellic acid treatment for double-purpose rice (Oryza sativa L.) varieties at different harvest times - Chenfei Dong; Nengxiang Xu; Chenglong Ding; Hongru Gu; Wenjie Zhang; Xianglin Li (Elsevier, 2016)
The purpose of this study was to investigate suitable gibberellic acid (GA) treatments for different rice (Oryza sativa L.) varieties when harvested at different times, and to supply instructions for improving double-purpose rice production. Four rice varieties (Wuyujing 3, Nanjing 44, Nanjing 46 and Liangyoupeijiu) were used in the experiment, with one GA spraying time in 2013 (the 15th day after anthesis) and three GA spraying times in 2014 (the 7th, 15th and 21st day after anthesis) being set, and the rice was harvested on two occasions in 2013 and 2014 (harvest time 1 when the grains of the control group plants had reached 80% maturity, and harvest time 2 occurring 6 days after harvest time 1). GA concentration was 45 g hm−2 in both years. The results indicated that at normal harvest time (harvest time 1), the optimum GA treatment for Liangyoupeijiu was an application on the 7th day after anthesis, but for Nanjing 44 and Nanjing 46, the optimum GA treatment was an application on the 21st day after anthesis. However, when harvest time was delayed (harvest time 2), GA applied on the 21st day after anthesis for Liangyoupeijiu, Wuyujing 3 and Nanjing 44 was the optimum GA treatment for both grain production and straw feed quality; while for Nanjing 46, GA applied on the 21st day after anthesis was the best GA treatment for grain yield, and GA applied on the 15th day after anthesis was the best treatment for straw feed quality. In conclusion, the optimum GA treatment for double-purpose rice changed when harvesting took place at different times, and it also changed for different rice varieties. Moreover, the GA effects on grain production and straw feed quality were sometimes different.